O DESEMPENHO DE MULTILÍNGUES EM TAREFAS DE CONTROLE INIBITÓRIO E DE PRIMING GRAFO-FÔNICO-FONOLÓGICO - Blank, Cintia Avila; Bandeira, Marta Tessman (Organon, 2011)
This paper presents the results of two studies carried out amongmultilingual participants: one of them dealing with inhibitory control ina task called Stroop Test, and the other one involving lexical access withrelated grapho-phonic-phonological priming. The first test was adminis-tered to 40 participants, 20 monolingual children speakers of BrazilianPortuguese (BP), and 20 multilingual children who speak Pomeranian orGerman (L1), BP (L2), and English (L3). The second task was performedby three multilingual adults who speak Portuguese (L1), French (L2) andEnglish (L3). The results of these two studies are discussed in light of theDynamic Systems theory.